THE STUDY OF PROFESSIONAL AND PSYCHOLOGICAL QUALITIES OF THE MANAGERS OF EDUCATION - Mesrobyan , V. M. (Modern Psychology, 2019)
The article summarizes the results of the expertise of professional and psychological qualities of the lecturers. Experts have highlighted the professional deep knowledge, communication ability, ability to analyze, aspiration for self-development, emotional stability as primary essential professional qualities.The lecturers also emphasized high intellect, honesty, delicacy, rhetorical ability, enthusiasm and sense of humor, but they did not consider them to be primary. The results indicate that the Armenian professors value the above mentioned professional psychological qualities. They are guided by the qualities that contribute to the effectiveness of the educational process.